Seedling developmental defects upon blocking CINNAMATE‐4‐HYDROXYLASE are caused by perturbations in auxin transport. Issue 6 (13th April 2021) - El Houari, Ilias; Van Beirs, Caroline; Arents, Helena E.; Han, Huibin; Chanoca, Alexandra; Opdenacker, Davy; Pollier, Jacob; Storme, Véronique; Steenackers, Ward; Quareshy, Mussa; Napier, Richard; Beeckman, Tom; et al.
Summary: The phenylpropanoid pathway serves a central role in plant metabolism, providing numerous compounds involved in diverse physiological processes. Most carbon entering the pathway is incorporated into lignin. Although several phenylpropanoid pathway mutants show seedling growth arrest, the role for lignin in seedling growth and development is unexplored. We use complementary pharmacological and genetic approaches to block CINNAMATE‐4‐HYDROXYLASE (C4H) functionality in Arabidopsis seedlings and a set of molecular and biochemical techniques to investigate the underlying phenotypes. Blocking C4H resulted in reduced lateral rooting and increased adventitious rooting apically in the hypocotyl. These phenotypes coincided with an inhibition in AUX transport. The upstream accumulation in cis ‐cinnamic acid was found to be likely to cause polar AUX transport inhibition. Conversely, a downstream depletion in lignin perturbed phloem‐mediated AUX transport. Restoring lignin deposition effectively reestablished phloem transport and, accordingly, AUX homeostasis. Our results show that the accumulation of bioactive intermediates and depletion in lignin jointly cause the aberrant phenotypes upon blocking C4H, and demonstrate that proper deposition of lignin is essential for the establishment of AUX distribution in seedlings. Our data position the phenylpropanoid pathway and lignin in a new physiological framework, consolidating their importance in plant growth and development.